Treating gastro-oesophageal cancer- a national comparison. (13th March 2011) - Neong, S F; Deacon, J; Sargeant, I R; Morris, D L
Abstract : Introduction: The incidence of gastric cancer is on decline but cases of oesophageal adenocarcinoma and junctional tumour are rising in UK. Patients present at a late stage, often preventing treatment with curative intent. A multidisciplinary approach is crucial in the management of these patients- primary chemoradiotherapy being the preferred treatment in squamous cell carcinoma. Methods: This retrospective study looked into the different treatment modalities in all 373 patients diagnosed with gastro-oesophageal cancers over the 5-year period from 1 January 2004 to 31 December 2008. Between the 2 district general hospitals in our NHS Trust, we cover a catchment population of 500 000. Data were obtained from endoscopy reports, computerised notes of the multidisciplinary team (MDT) meetings and patients' medical notes. Results: 139 and 234 patients were diagnosed with gastric and oesophageal cancer respectively over the 5-year period. 66% (245) of them were male. Oesophageal biopsies revealed 149 cases of adenocarcinoma and 69 cases of squamous cell carcinoma. Mean age of diagnosis of oesophageal cancer was 73 (43–93) and 76 (40–95) for gastric cancer. Staging modality of choice includes computerised tomography (CT) scans, positron emission tomography (PET) scans and endoscopic ultrasound (EUS) in selected patients. All of our patients had staging CT. 52 (22%) patients with oesophageal cancer underwent Ivor Lewis oesophagectomy (10 without neoadjuvant chemotherapy) and 19 (8%) patients had primary chemoradiotherapy as their mode of treatment. 1 patient had Halo treatment. For gastric cancer, 45 (32%) patients underwent partial/total gastrectomy with curative intent. The remainder had palliative surgical and/or oncological treatment as well as endoscopic therapy including stenting, dilatation and laser recannulation. Conclusion: Only a third (33% for gastric cancer and 30% for oesophageal cancer) of all patients diagnosed with gastro-oesophageal cancers in 2004–2008 had curative treatment. Our findings mirror the figures in the recently published National Oesophago-Gastric Cancer Audit 2010 where overall, 36% of patients had curative treatment. The majority of our patients with gastric cancer (66%) were treated palliatively compared to 50% nationally. The number of patients treated with curative intent appears to be waning partly due to the increased use of PET scans and EUS in identifying more advanced disease.